Features of scientific criticism within the framework of the presence of a single critical approach PhD thesis (Structural criticism from theory to practice) as an example - Rebeen Khaleel Qader; Sardar Ahmad Hasan (Zanco Journal of Humanity Sciences)
Scientific criticism is the criticism that relies on the mechanism, hypothesis, and scientific method used to study, analyze, and interpret literary texts. One of the most important characteristics of scientific criticism is putting the emphasis on methodological research and the use of critical research. An attempt has been made to put this research forward towards academic and objectivity. This paper is an attempt to clarify the features and manifestations of scientific criticism, especially at a level where a single approach to criticism is used within the scope of critique. This paper consists of an introduction and two main parts, and finally the results and list of sources are presented.